Student Perceptions Of Infographic Poster Media For Arabic Lexicography Course - Che Hat, Norhayati Binti; Radzi, Majdan Bin Paharal; Bin Abdul Hamid, Mohd Fauzi Binti; Binti Mohmad Rouyan, Nurazan Isiaq; Binti Sulaiman, Suzana (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Teaching and learning Arabic Lexicography requires a creative and innovative approach to improve learning effectiveness. Using infographic posters as instructional resources is an innovative approach that could render the classroom more engaging and spark students' interest. The objective of this study was to determine students’ perceptions about the use of infographic posters in Arabic Lexicography courses. This quantitative study included 84 UniSZA students and collected data through a questionnaire. The descriptive analysis was performed using SPSS version 26.0. The study's results showed that students' perceptions of using infographic posters in Arabic Lexicography courses were generally positive, with a mean score ranging from 4.60 to 4.63. As a result of their ability to boost student comprehension, interest, and motivation, infographic posters were deemed appropriate for use as educational materials. This study would help Arabic language lecturers expand their methods of instruction. According to this study, infographic posters should be used more frequently in other Arabic language classes and as resources to help create more engaging and successful curricula.